2015
DOI: 10.1093/annonc/mdv253
|View full text |Cite
|
Sign up to set email alerts
|

Derived neutrophil lymphocyte ratio may predict benefit from cisplatin in the advanced biliary cancer: the ABC-02 and BT-22 studies

Abstract: These data confirm that high dNLR is associated with worse OS and PFS, and suggests it may also be predictive of benefit for the addition of cisplatin to gemcitabine in European patients with ABC. Incorporating dNLR into the clinical context may better inform prognosis and chemotherapy decisions in ABC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 20 publications
2
62
0
Order By: Relevance
“…investigated a total of 162 patients with metastatic colorectal cancer who received palliative chemotherapy and reported that patients with pretreatment NLR values of > 5 that decreased to ≤5 before the second chemotherapy cycle showed a significantly longer progression-free survival and a trend towards longer OS compared with patients with a persistent NLR of > 5. Data in patients with oesophageal and biliary cancer have also suggested an association between the NLR and response to cisplatin-based chemotherapy [38, 39]. These results indicated that the NLR was predictive for the prognosis and response to chemotherapy regardless of tumour origin.…”
Section: Discussionmentioning
confidence: 94%
“…investigated a total of 162 patients with metastatic colorectal cancer who received palliative chemotherapy and reported that patients with pretreatment NLR values of > 5 that decreased to ≤5 before the second chemotherapy cycle showed a significantly longer progression-free survival and a trend towards longer OS compared with patients with a persistent NLR of > 5. Data in patients with oesophageal and biliary cancer have also suggested an association between the NLR and response to cisplatin-based chemotherapy [38, 39]. These results indicated that the NLR was predictive for the prognosis and response to chemotherapy regardless of tumour origin.…”
Section: Discussionmentioning
confidence: 94%
“…26,27 These might partially explain why an elevated NLR is associated with poor survival. Recent clinical studies revealed that dNLR was associated with chemotherapy response 10,28 and prognosis in many advanced cancers, such as metastatic melanoma, 8 metastatic castration-resistant prostate cancer, 9 advanced biliary cancer, 10 and advanced colorectal cancer. 29 The dNLR is composed of WBCs and neutrophils; this parameter has been proposed as an alternative to NLR for studies where only WBCs and neutrophils have been recorded.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] In particular, the neutrophil to lymphocyte ratio (NLR), which is considered as a biomarker of SIR, has emerged as an independent prognostic factor for biliary tract cancer in operable patients and in advanced disease patients undergoing adjuvant therapy. 12,13 The lymphocyte to monocyte ratio (LMR) is another biomarker of SIR, with a combination of lymphocyte count and monocyte count. The LMR as a prognostic factor for patients with colorectal cancer and hepatocellular carcinoma was recently investigated in a number of studies.…”
Section: Introductionmentioning
confidence: 99%